Photophysics of Molecular-Weight-Induced Losses in Indacenodithienothiophene-Based Solar Cells - Gasparini, Nicola; Katsouras, Athanasios; Prodromidis, Mamantos I.; Avgeropoulos, Apostolos; Baran, Derya; Salvador, Michael Filipe; Fladischer, Stefanie; Spiecker, Erdmann; Chochos, Christos L.; Ameri, Tayebeh; Brabec, Christoph (Advanced Functional Materials, 2015)
The photovoltaic performance and optoelectronic properties of a donor-acceptor copolymer are reported based on indacenodithienothiophene (IDTT) and 2,3-bis(3-(octyloxy)phenyl)quinoxaline moieties (PIDTTQ) as a function of the number-average molecular weight (Mn). Current-voltage measurements and photoinduced charge carrier extraction by linear increasing voltage (photo-CELIV) reveal improved charge generation and charge transport properties in these high band gap systems with increasing Mn, while polymers with low molecular weight suffer from diminished charge carrier extraction because of low mobility-lifetime (μτ) product. By combining Fourier-transform photocurrent spectroscopy (FTPS) with electroluminscence spectroscopy, it is demonstrate that increasing Mn reduces the nonradiative recombination losses. Solar cells based on PIDTTQ with Mn = 58 kD feature a power conversion efficiency of 6.0% and a charge carrier mobility of 2.1 × 10-4 cm2 V-1 s-1 when doctor bladed in air, without the need for thermal treatment. This study exhibits the strong correlations between polymer fractionation and its optoelectronics characteristics, which informs the polymer design rules toward highly efficient organic solar cells.
Keywords: charge transport; energetic losses; indacenodithienothiophene; molecular weight; organic solar cells